Advances in diagnosis and treatment of mental disorders - Heitzman, Janusz (Przewodnik Lekarza/Guide for GPs, 2011)
The past 10 years is often referred to as the decade of the brain. This is due to the specific acceleration of research that was built on the achievements of new diagnostic techniques, neuroimaging, genetics, and psychopharmacology, which in turn pushed current knowledge of the pathogenesis of mental disorders and the options to treatment in new directions. This is reflected in the development of new classifications of mental disorders, where the emergence of new disease entities, they change their criteria for recognizing and advancing the standards of treatment for them. The aim of this papers is to show the opportunity of increasing the precision of the psychiatric diagnosis by the use of new possibilities of “dimensional assessment” and the inclusion of items of information in the diagnosis neurobiological, genetic, and endophenotypes. Research of causes concerning both well-known for a long time and new psychiatric disorders refute myths about the fossilized capabilities of psychiatric diagnosis, which is neither modern nor effective treatment.